(untitled) (UNIZIK Journal of STM Education, 2026)
The study investigated the predictive influence of attribution styles on secondary school students’ academic achievement in Biology. Three research questions, guided the study, with three null hypotheses tested at 0.05 alpha levels. A co-predictive research design was adopted. A sample of 594 SS2 students, drawn from the 24,102 Senior Secondary Year Two (SS2) students offering Biology in Anambra State, was drawn using multistage sampling procedure. Two instruments: Attribution Styles Questionnaire (ASQ) and Biology Score Proforma (BSP), containing students’ achievement scores in biology, for the 2024/2025 academic session, were used for data collection. The adapted instrument (ASQ) validated by three expects was subjected to reliability testing, using Cronbach alpha method, to yield a coefficient value of 0.87. Data collected were analyzed using regression analyses. The findings revealed among others that attribution styles accounted for 9.4% variance in students’ academic achievement in Biology. On gender, the study revealed that while attribution styles significantly contributed to male students’ academic achievement, the contrary were recorded for the female students. Furthermore, the study revealed that attribution styles is a significant predictor of secondary school students’ academic achievement in Biology. On relative contributions of individual dimensions of attribution styles, the study revealed that all the dimensions of attribution styles individually and jointly, significantly predicted students’ academic achievement in biology, except for internal versus external dimension of attribution styles. Based on the findings, it was recommended among others that Biology teachers should encourage students to develop positive attribution styles by helping them associate academic success with effort, determination, and effective study practices.